Community Empowerment through the Development of Langkuik Indah Waterfall Nature Tourism in Nagari Sikucur Timur, West Sumatra - Awalina, Rahmi; Fiana, Risa Meutia; Febrina, Ria (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2025)
Community-based tourism development is one of the important efforts in improving the local economy and environmental sustainability. Langkuik Indah Waterfall in Nagari Sikucur Timur, Padang Pariaman Regency, has great potential to become a leading tourist destination. However, various challenges in its management, such as the lack of community capacity in managing tourist attractions, the lack of utilization of information technology, and the absence of solid institutions, are the main obstacles in the development of this tourism. This community service activity aims to empower local communities in natural tourism management through training and improving digital promotion. The results of this activity show an increase in the capacity of the community in managing tourism objects, increasing the use of social media in tourism promotion. The strategic plan for tourism development developed with the community is expected to be the basis for sustainable and competitive tourism management.